(untitled) (Al-Farooq Journal of Sciences, 2026)
Contemporary human thought is undergoing profound transformations that have brought the question of the human being back to the forefront as a central philosophical concern intersecting with the humanities, scientific developments, and technological innovations. Amid the growing dominance of instrumental rationality, rapid advances in artificial intelligence, and the expansion of the digital revolution, there is an increasing need to reconsider the epistemological role of philosophy—not merely as a contemplative discourse, but as a critical intellectual practice capable of questioning prevailing modes of thought and reconstructing the relationship between human beings, knowledge, and the world. This study is grounded in the assumption that restoring the centrality of the question of the human being constitutes a fundamental condition for revitalizing the epistemic function of philosophy and transforming it into a knowledge-producing practice that moves beyond interpretation toward critique and theoretical reconstruction. Accordingly, the study examines the conceptual foundations of the question of the human being, explores the dialectical relationship between philosophical inquiry and critical thinking, and investigates how philosophy can generate new epistemological frameworks capable of addressing contemporary civilizational challenges, including value crises, digital transformations, and issues of identity and meaning. Methodologically, the study adopts a critical-analytical approach, supported by the historical method to trace the evolution of the question of the human being across major philosophical traditions, and the comparative method to examine different philosophical conceptions of the role of philosophy in the production of knowledge. The study concludes that the contemporary significance of philosophy lies not in providing definitive answers, but in its capacity to formulate foundational questions, deconstruct closed epistemic structures, and cultivate a critical rationality capable of engaging with the complexity of the human condition. Consequently, restoring the question of the human being represents a vital pathway toward renewing the philosophical project and promoting an open, human-centered form of knowledge that integrates critique, responsibility, freedom, and creativity in response to the challenges of the contemporary world.